The Interaction Mechanism of Papaya Seeds (Carica papaya L.) as a Natural Coagulant and Remazol Red Under Different pH Conditions - Dewi, Vina Melinda Inka; Rahmayanti, Maya (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2022)
Batik wastewater contains a high concentration of dye that comes from the batik dyeing process. In this study, papaya seeds were applied as a natural coagulant to reduce the concentration of remazol red in batik wastewater. Dried papaya seeds were characterized using Fourier Transform Infrared Spectroscopy (FTIR). The coagulation method used the batch method in the pH range of 1-6. The FTIR spectra showed that the papaya seeds contained compounds with -NH2 and -COOH functional groups. The results of coagulation showed that the pH of batik wastewater had an effect on the ability of papaya seeds to reduce the concentration of remazol red. The optimum pH condition was obtained at pH 2 with a decrease in the concentration of remazol red by 96.1%. The interaction that occurs between the coagulant of papaya seeds and the remazol red of batik wastewater is through electrostatic interactions.